Effects of Functional Training, Compared to Traditional Strength Training, on Physical Fitness in Older Adults: A Systematic Review - Erices-Olivo, Juan (2023)
Introduction: Older adults (OA) represent a growing population group that is especially susceptible to a loss of physical fitness associated with functional impairment. Traditional resistance training (TRT) has proven to be effective, improving or limiting the loss of muscle mass and frailty. Functional training (FT) has emerged as an affordable alternative to prevent physical changes caused by aging. However, there is little evidence regarding the effectiveness of functional training, versus traditional resistance training, on physical capacity in older adults. Purpose: To systematically review the effectiveness of FT, compared to TRT, on improving physical fitness in OA. Methodology: Pubmed, SPORTDiscus (EBSCO), SCOPUS, PEDro, and Web of Science databases were consulted. In addition, search strategies were performed, including the terms "resistance training," "aged," "physical fitness," and "functional training." Results: Five articles meeting inclusion criteria were identified. From the qualitative analysis conducted, it was observed that both FT and TRT training are effective in improving various manifestations of strength. In addition, compared to TRT, FT presents a higher proportion of effectiveness on functional fitness elements such as cardiorespiratory capacity (3.3 times), agility (2.7 times), and functional lower body strength (1.7 to 2.8 times). Conclusion: Both FT and TRT can be valid alternatives to improve general physical fitness in OA. Likewise, EF is more effective on parameters related to functionality in OA.